The approximate functional equation of Hecke’s Z-functions for the algebraic quadratic imaginary number fields - Bulota, K. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:К. Булота. Приближенное функциональное уравнение Z-функций Гекке мнимого квадратичного поляK. Bulota. Hekės Z-funkcijų artutiniai funkcionalinė lygtis kvadratinio menamo kūno atveju